2000
DOI: 10.1054/bjoc.1999.0881
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to heat shock protein 90 in osteosarcoma patients correlate with response to neoadjuvant chemotherapy

Abstract: Autoantibodies to the heat shock protein 90 (Hsp 90) have been reported as prognostic marker in breast cancer patients. Sera from 20 high-grade osteosarcoma patients were tested at the time of diagnosis by enzyme-linked immunosorbent assay. Presence of anti-Hsp90 antibodies correlated with a better response to neoadjuvant chemotherapy (P< 0.01), whereas the absence correlated with development of metastases. These data suggest that anti-Hsp90 antibodies might be of predictive value in human osteosarcoma. © 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Well-established clinical factors are rather confined to age [2,3,7], tumour site [2,7], size [3,6] and response rate [2][3][4][5][6][7], with the latter being observed as the most reliable indicator [5]. Similarly, controversial evidence is reported for serological markers such as alkaline phosphatase or lactate dehydrogenase [3,6,8] while different molecular factors prove to be of rather reproducible predictive value, including, among others, human epidermal growth factor receptor 2 (HER2), vascular endothelial growth factor (VEGF), pglycoprotein, transmembrane glycoprotein ErbB-2, chemokine receptor, matrix metalloproteinases (MMPs), livin, ezrin or heat shock proteins [8,9,[31][32][33]. Though, their measurement is to some extent time-consuming and complex and therefore often not integrated into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Well-established clinical factors are rather confined to age [2,3,7], tumour site [2,7], size [3,6] and response rate [2][3][4][5][6][7], with the latter being observed as the most reliable indicator [5]. Similarly, controversial evidence is reported for serological markers such as alkaline phosphatase or lactate dehydrogenase [3,6,8] while different molecular factors prove to be of rather reproducible predictive value, including, among others, human epidermal growth factor receptor 2 (HER2), vascular endothelial growth factor (VEGF), pglycoprotein, transmembrane glycoprotein ErbB-2, chemokine receptor, matrix metalloproteinases (MMPs), livin, ezrin or heat shock proteins [8,9,[31][32][33]. Though, their measurement is to some extent time-consuming and complex and therefore often not integrated into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, overexpression of HSP70 and HSP90 correlates with poor prognosis (37,38). Overexpression of HSPs also contributes to drug resistance and a poor response to combination chemotherapy (39)(40)(41)(42). HSF1 is the master regulator of the heat shock response in eukaryotes, a highly conserved protective mechanism against heat stimulation (43).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of hsp90 autoantibodies and late stage ovarian cancer implies that it may have utilities as a novel prognostic biomarker for ovarian cancer. In osteosarcoma, hsp90 autoantibody positivity has been found to be associated with response to chemotherapy, whereas, its absence correlates with metastasis (Trieb et al, 2000). In contrast, Conroy et al (1998) reported that the presence of hsp90 autoantibodies indicated metastasis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%